2018
DOI: 10.1089/can.2018.0043
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ingestion of Cannabis sativa: Risks, Benefits, and Effects on Malaria-Infected Hosts

Abstract: Background: The emergence of a multidrug-resistant strain of Plasmodium falciparum (Pf Pailin) raises concern about malaria control strategies. Unfortunately, the role(s) of natural plants/remedies in curtailing malaria catastrophe remains uncertain. The claims of potential antimalarial activity of Cannabis sativa in vivo have not been well established nor the consequences defined. This study was, therefore, designed to evaluate the effects of whole cannabis consumption on malaria-infected host.Methods: Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…In mice infected with Plasmodium berghei, antiparasitic properties of C. sativa were not comparable with that of chloroquine, but results suggested the potential of cannabis in reducing pathogenicity and enhancing disease tolerance [121].…”
Section: Parasite Infectionsmentioning
confidence: 91%
See 1 more Smart Citation
“…In mice infected with Plasmodium berghei, antiparasitic properties of C. sativa were not comparable with that of chloroquine, but results suggested the potential of cannabis in reducing pathogenicity and enhancing disease tolerance [121].…”
Section: Parasite Infectionsmentioning
confidence: 91%
“…4-acetoxycannabichromene, 5-acetyl-4-hydroxycannabigerol, and -1′S hydroxycannabinol have showed mild-to-moderate antimalarial activity in vitro [ 119 , 120 ]. In mice infected with Plasmodium berghei, antiparasitic properties of C. sativa were not comparable with that of chloroquine, but results suggested the potential of cannabis in reducing pathogenicity and enhancing disease tolerance [ 121 ].…”
Section: Cannabinoids In Medicinementioning
confidence: 99%
“…On the other hand, in vitro studies demonstrated that cannabinoids exert microbicidal activity on different bacteria and fungi [ 65 , 68 ] and could also control viral pathogenesis in some cases [ 69 , 70 , 71 ]. In a murine model for Malaria, oral administration of Cannabis increased the survival of infected mice [ 72 ]. In addition, Batugedara et al observed increased levels of endocannabinoids in the lung and intestine of helminths infected mice and demonstrated that this elevation was associated with improved host immunity [ 73 ].…”
Section: The Effects Of Cannabinoid-based Treatments In Different mentioning
confidence: 99%
“…126 Malaria is another zoonosis with great research potential as very few cannabis studies couple public health with veterinary medicine (in 2017 alone, there were 219 million cases and 435,000 deaths, with allocated resources of US$3.1 billion). [127][128][129][130][131]…”
Section: Leishmaniasis and Malariamentioning
confidence: 99%